مستوى المهارات الحياتية لدى طلبة كلية التربية - جامعة تعز - الأثوري، سميحة سعيد عبدالله عبدالرب (جامعة تعز - مركز التأهيل والتطوير التربوي, 2023)
هدف هذا البحث إلى معرفة مستوى المهارات الحياتية لدى طلبة كلية التربية- جامعة تعز، ومعرفة دلالة الفروق في مستوى هذه المهارات بحسب المستوى الدراسي والتخصص العلمي ولتحقيق أهداف البحث تم استخدام مقياس المهارات الحياتية مكون بصورته النهائية من (86) فقرة موزعة على سبعة محاور هي مهارات حل المشكلات واتخاذ القرار، ومهارات التفكير، ومهارات الاتصال والتواصل، ومهارات العمل الجماعي والتعاون، والمهارات الأكاديمية (الدراسية)، والمهارات التكنولوجية (التقنية)، والمهارات الصحية والبيئية. وقد تم التحقق من الخصائص السيكومترية للمقياس المتمثلة بالصدق والثبات، واستخدم المنهج الوصفي المسحي، وتكونت عينة البحث من (158) طالبا وطالبة من طلبة المستويين الأول والرابع في الأقسام العلمية الثلاثة (البيولوجي، والكيمياء، والفيزياء)، وأظهرت النتائج أن مستوى المهارات الحياتية لدى عينة البحث كان متوسطا، وأنه توجد فروق دالة إحصائيا في هذا المستوى تبعا لمتغير المستوى الدراسي (الأول، والرابع) ولصالح طلبة المستوى الرابع، بينما لا توجد فروق دالة إحصائيا في هذا المستوى تبعا لمتغير التخصص (البيولوجي، والكيمياء، والفيزياء). The aim of this research is to know the level of life skills among students of the College of Education- Taiz University, and the differences in the level of these skills according to academic level and scientific specialization. To achieve the objectives of the research, the life skills scale was used in its final form of (86) items distributed on seven axes: problem-solving and decision-making skills, thinking skills, communication and communication skills, teamwork and cooperation skills, academic skills, Technological skills, health and environmental skills. The researcher verified the psychometric properties of the scale and used the descriptive survey method, and the research sample consisted of (158) male and female students from the first and fourth level students in the three scientific departments (Biology, Chemistry, Physics) at the College of Education- Taiz University. The results of the research showed that the level of life skills of the students in the research sample was average, and that there were statistically significant differences on the life skills scale according to academic level (first- fourth) in favor of the fourth level students, and there were no statistically significant differences on the life skills scale according to Specializations (Biology, Chemistry, Physics).
Keywords: المهارات الحياتية -- تنمية المهارات -- العمليات العقلية -- الأنشطة التعليمية -- طلبة الجامعات